The Role of Reconciliation Committee in the Reconciliation of Domestic Violence in the Center of Erbil City - Rasty Ghafoor Fettah; Shvan Ismail Hamad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This research has been conducted under the title (The Role of Competent Committee in the Reconciliation of Domestic Violence in the Center of Erbil City). The committee was founded after the legislation on anti-domestic violence law which consists of seven articles, article five of which refers to the establishment of a committee to reconcile domestic violence. The members of the committee must be experienced people and a significant part of the mediation roles and responsibilities of the committee must be devoted to social workers. The current study first tries to identify the roles of the social workers in the reconciliation and mediation of domestic violence, the most important characteristics of the committee and its effects on families. Besides, it attempts to find out the duties and responsibilities of the committee as well as its impact on the members and the environment of the families with problems. This study consists of an introduction, three chapters, and a list of bibliography. The first chapter highlights the importance of the study, the objectives of the study, and the problem of the study. Chapter two includes the key terms, methodology, data collection instruments, and the research challenges. Chapter three displays the analysis of the study results, conclusion, suggestions, and recommendations.